Characterisation of systems of potato's crops at Imanan in Tillaberi region western Niger - Thèsard, Moussa Soumaila Mamane Bachir; Issa ADAMOU,; Zoubeirou ALZOUMA MAYAKI, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2024)
The potato is getting a real success at Imanan, with about 18500 tonnes harvested in 2023, that to say a normal progression under some years. Today the potato is the first vegetable crop at Imanan where its dedicated areas increase had exceeded that of all the other vegetable crops. But it is unfortunately the prey of a lot of destructive which cause damages and compromise the harvests , among them we can find the nematodes. The aim of this article is to contribute to the improvement of the productivity ofthe potato's crops. The methodology has consisted in leading maintenance, in survey and the observation of local cultural practices ( land preparation, tuber's fragmentation after pre_ germination, hilling, fertilisation) for the potato's culture period the plurality of harvest for the two cultural cycles is of 66 tonnes against 33 tonnes of the normal cycle. On the other side the selling price of the kg of first December and the lateMarch were400 and 200 CFA per kg whereas the production is ceded at 200 CFA per kg because the offer exceeded the needs. It is clearly establish that the practice of the two yearly cycles obtain more products and incomes. In general the production nature ( consumption and conservation...) guided the choice of varieties.But at Imanan the potato's production is done in preference with Rosanna variety. By the means of caliberer, five(5) classes have been differenciated. Since its introduction around 1952 at Imanan, the potato has known an considerable boom whether in the cultivated area or in the food habits. It is cultivable during almost six(6) months and virtually all over the Imanan Canton. The potato's culture contribute more and more on the world food offer and its consumption is more than doubled in the last thirty (30) years.